(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: The expert evidence is perhaps one of the most costly and time-consuming means of evidence. However, a consistent expert opinion is decisive. Still, the evaluation of it has always been an argued issue. With the change of the procedural rules’ legal practice got answers to many questions while new questions have arisen. In the heart of changes are the rules of expert evidence in actions related to personal status. Methodology: In addition to the identification of the need of change coming from the legal practice, this study analyses the direction, significance and effect of the change. Findings: The actions related to personal status require different approach from the property disputes. In doing so formalised solutions mean the rapidity. Personalised method of taking of evidence still needs a high degree of flexibility. Value: This study can only define tendencies. The correctness of these tendencies shall be judged by the results of the practice. Still, the most important is to achieve a broader evaluating analysis of the expert evidence.